Data on Safety of Intravaginal Boric Acid Use in Pregnant and Nonpregnant Women: A Narrative Review. Issue 12 (23rd December 2021) - Mittelstaedt, Rachel; Kretz, Alyssa; Levine, Michael; Handa, Victoria L.; Ghanem, Khalil G.; Sobel, Jack D.; Powell, Anna; Tuddenham, Susan
Abstract : This study is a narrative review summarizing available data on the safety of intravaginal boric acid use for women and in the setting of pregnancy. Supplemental digital content is available in the text. Abstract: Intravaginal boric acid (IBA) represents one of the only options available to treat azole-resistant vulvovaginal candidiasis (VVC) and is included as part of multiple national guidelines (including the United Kingdom and the United States) for the treatment of VVC or recurrent bacterial vaginosis. Novel products using IBA are under development for treatment and suppression of VVC and bacterial vaginosis. Use of over-the-counter or clinician-prescribed IBA in reproductive-aged women is already widespread and may increase further if drug resistance in VVC rises. However, IBA is not a Food and Drug Administration–approved drug, and safety data are sparse. Given these factors, it is important to understand the currently available data on the safety of IBA use. Herein, we set out to synthesize human and animal data (converting, where appropriate, dose and serum values to standard units to facilitate comparison) to answer 2 key questions: (1) What are the data on the safety of IBA use for women? and (2) What are the data on the safety of IBA use in pregnancy? We find that, despite gaps, available data suggest IBA use is safe, at least when used in doses commonly described in the literature as being prescribed by clinicians. Information on harms in pregnancy is limited, and data remain insufficient to change current guidelines, which recommend IBA avoidance in pregnancy.